比較技術倫理學視域下的腦機介面技術: Brain-Computer Interface Technology in the Context of Comparative Technology Ethics - LIU, Jiabao (International Journal of Chinese & Comparative Philosophy of Medicine, 2023)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. Zhai Zhenming compares brain–computer interface (BCI) technology with artificial intelligence technology and other mind extension technologies (such as ChatGPT), which I refer to as “comparative technology ethics.” I believe that it is meaningful to conduct research using comparison in the field of bioethics or technical ethics. I attempt to develop this type of comparative research and propose a comparison between risk-in-experiment technology and risk-of-effect technology. Although in some respects BCIs fall into the first category, the question of whether BCIs should be prohibited should be analyzed on a case-by-case basis.